2021
DOI: 10.3390/su13041814
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Validation of Social Media as an Educational and Professional Tool Student Perceptions Scale (SMEPT-SPS)

Abstract: Although social media has an increasing presence both in university and sports settings, in the sports-management education context, no instruments (without being focused on one particular social-media platform, e.g., Facebook and Twitter) have been developed and validated that globally allow the academy to explore the perceptions of sports-management students concerning the educational and professional learning potential that these tools offer. Therefore, this research’s main objective is to develop and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
0
2
0
6
Order By: Relevance
“…With this in mind, learners are utilizing their perceived appropriate media type for a task. For instance, TikTok for short video-based work and Facebook or WeChat for managing group conversations and meetings ( 11 , 12 ). The opportunity for knowledge-sharing notwithstanding, students have the capacity to use such resources for knowledge generation, external feedback, and learning opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, learners are utilizing their perceived appropriate media type for a task. For instance, TikTok for short video-based work and Facebook or WeChat for managing group conversations and meetings ( 11 , 12 ). The opportunity for knowledge-sharing notwithstanding, students have the capacity to use such resources for knowledge generation, external feedback, and learning opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Los medios sociales están cada vez más presentes en la vida de las personas, siendo herramientas muy valoradas por los empleadores de la industria del deporte (López-Carril et al, 2021). Si bien medios sociales como Facebook y Twitter han recibido una gran atención por parte de los académicos (Manca & Ranieri, 2016), otros medios sociales que ofrecen oportunidades de aprendizaje para el alumnado como LinkedIn, Pinterest o TikTok, han recibido una menor atención.…”
Section: Fundamentación Teóricaunclassified
“…Si bien medios sociales como Facebook y Twitter han recibido una gran atención por parte de los académicos (Manca & Ranieri, 2016), otros medios sociales que ofrecen oportunidades de aprendizaje para el alumnado como LinkedIn, Pinterest o TikTok, han recibido una menor atención. En un contexto de pandemia causado por la expansión del virus SARS-CoV-2, los medios sociales se han convertido en un recurso para el profesorado a la hora de generar espacios de enseñanza-aprendizaje en línea, facilitando que el desarrollo de las clases siga su curso superando las posibles limitaciones y restricciones a las clases presenciales (López-Carril et al, 2021).…”
Section: Fundamentación Teóricaunclassified
See 1 more Smart Citation
“…For example, the use of social media applications by students has skyrocketed (from 11% in 2005 to 90% in US adults aged 18-29 (Mahdiuon et al, 2020), and the impact on academic performance has varied (Kulidtod and Pasagui, 2017). In educational environments, students may use social media for a variety of purposes, including knowledge finding, collaboration, and social interaction (Elsayed, 2016;Rasheed et al, 2020;López-Carril et al, 2021;Karakose et al, 2022a). Several studies have shown a connection between social media use and undergraduate university students' academic performance and achievement (Alnjadat et al, 2019;Al-Maatouk et al, 2020a;Al-Rahmi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%